2009
DOI: 10.1159/000210057
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Pineal and Related Tumors

Abstract: Radiosurgery is increasingly being used to treat pineal region tumors, either as an additional therapy after conventional treatments or as a primary treatment. We report our experience with Gamma Knife radiosurgery (GKRS) for the treatment of pineal and related tumors. Forty-nine patients underwent GKRS for pineal and related tumors (n = 74) between February 1992 and September 2007. The diagnosis was germ cell tumors (GCTs) in 38 patients (53 tumors), pineal parenchymal tumors (PPTs) in 9 (19 tumors), and unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 21 publications
0
34
1
Order By: Relevance
“…The male:female ratio in our patients was 15:2, which suggests that radiosensitive PRTs may have accounted for the majority of cases. According to this cha racteristic and preoperative imaging evaluations, we selected midrange doses for GKS compared to previous studies 20,23 . Another factor was the minimal invasiveness of GKS.…”
Section: Discussionmentioning
confidence: 99%
“…The male:female ratio in our patients was 15:2, which suggests that radiosensitive PRTs may have accounted for the majority of cases. According to this cha racteristic and preoperative imaging evaluations, we selected midrange doses for GKS compared to previous studies 20,23 . Another factor was the minimal invasiveness of GKS.…”
Section: Discussionmentioning
confidence: 99%
“…SRS has also been described for pineal region tumors and PPTs specifically. Gamma Knife radiosurgery, which involves the application of a skull mounted frame to achieve stereotaxis, has been shown to be particularly effective in controlling the growth of low-grade pineocytomas with reported rates of local tumor control of 85 to 100% [9,13]. Tumor control rates for the more aggressive PPTIDs and pineoblastomas was reported to be about 30% in one series [13].…”
Section: Discussionmentioning
confidence: 99%
“…Sarkar (Sarkar et al, 2002) and Kano (Kano et al, 2009c) reported two GKRS studies on 18 and 30 patients affected with oligodendrogliomas and mixed oligodendroastrocytomas, respectively, but both series included low-and high-grade tumors. As concerns the unusual primitive neuroepithelial tumors of the brain, the largest published series always comprised low-and high-grade tumors (Kano et al, 2009d, Mori et al, 2009, Lekovic et al, 2007, Hasegawa et al, 2002, Kobayashi et al, 2001, while the studies with exclusively unusual LGPNTs were always represented by a few cases (usually, less than 15). To our knowledge, the work of our team represent the largest series of unusual LGPNTs treated with stereotactic radiosurgery.…”
Section: Overall Seriesmentioning
confidence: 99%
“…As concerns outcome results ( ranged between 87.5% and 100%. Mori (Mori et al, 2009) is the only author who reported a 10-year actuarial survival rate of 67%. In our series, the 10-year actuarial survival rate was 92%.…”
Section: Pineocytomamentioning
confidence: 99%
See 1 more Smart Citation